Community Empowerment through the Production of Cost-Effective Liquid Detergent with Competitive Quality in Ogan Ilir Regency - Yulianita, Anna; Rohima, Siti; Utami, Puspa; Desmanita, Wiga Ayu; Hermawati, Lisa; Azzahrah, Meidiana; Rhani, Nanda Muthiah; Bissalamy, Haqqie Muflicha; Pratama, Doyoba Sie; Habibi, Kamil (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance residents’ skills and economic independence through training in the production of cost-effective and environmentally friendly liquid detergent. The program involved 25 participants, comprising housewives and micro-entrepreneurs in Ogan Ilir Regency. A participatory approach was employed, consisting of socialization, technical production training, and continuous mentoring stages. Evaluation was conducted using an assessment sheet divided into two components: evaluation of program implementation and evaluation of its impact on participants’ business development. A Likert-scale-based assessment was used to measure participants’ levels of understanding, satisfaction, and motivation, while the data were analyzed descriptively using Microsoft Excel. The results indicate that participants acquired a solid understanding of liquid detergent production, including ingredient formulation, mixing techniques, and product packaging. In addition to technical skill development, the training enhanced participants’ entrepreneurial awareness, production efficiency, and understanding of the economic potential of household-based products. The evaluation findings demonstrate a significant increase in community knowledge and motivation to develop independent businesses, although further mentoring in technical refinement and marketing strategies remains necessary. This program aligns with the objectives of the Sustainable Development Goals (SDGs), particularly those related to poverty alleviation, decent work, and sustainable consumption and production. With continued support from higher education institutions and local governments, this initiative is expected to serve as a model for sustainable village economic empowerment and contribute to improving community welfare.